Impact of extreme prematurity, chorioamnionitis and sepsis on neonatal monocyte characteristics and functions - Khaleda Rahman Qazi; Dhanapal Govindaraj; Magalí Martí; Ymke de Jong; Georg Bach Jensen; Thomas Abrahamsson; Maria C. Jenmalm; Eva Sverremark-Ekström (Karger Publishers, 2024)
Introduction: The innate branch of the immune system is important in early life, in particular for infants born preterm. Methods: We performed a longitudinal analysis of the peripheral monocyte compartment in extremely preterm children from a randomized placebo-controlled study of probiotic supplementation. PBMCs and fecal samples were collected at several timepoints during the first months of life. Monocyte characteristics were analyzed by flow cytometry and LPS-stimulated PBMC culture supernatants were analyzed by Luminex or ELISA. Plasma cytokines and gut microbiota composition were analyzed by ELISA and 16S rRNA-sequencing, respectively. Results: The extremely preterm infants had persistent alterations in their monocyte characteristics, that were further aggravated in chorioamnionitis cases. They showed a markedly reduced TLR4 expression and hampered LPS-stimulated cytokine responses 14 days after birth. Notably, at later time-points, TLR4 expression and LPS-responses no longer correlated. Sepsis during the first weeks of life strongly associated with increased proinflammatory, and reduced IL-10, responses also at post menstrual week 36. Further, we report a correlation between gut microbiota features and monocyte phenotype and responses, but also that probiotic supplementation associated with distinct monocyte phenotypic characteristics, without significantly influencing their responsiveness. Conclusion: Extremely preterm infants have monocyte characteristics and functional features that deviate from infants born full-term. Some of these differences persist until they reach an age corresponding to full-term, potentially making them more vulnerable to microbial exposures during the first months of life.